Evaluation of Investor Awareness on Techniques used in Stock Trading before their Investment - Vidhya, B; Magesh, S (International Journal of Engineering and Technology, 2018)
Indian stock exchange is one of the world’s largest stock market. It holds 16,993,616 active demat account investors as on February 2018, where the investor trade the equities. An equity holding will make the investor to own a percentage of the company’s capital. The value of the investment raise as the company develops, initially it starts with Initial Public Offering (IPO) which will be allotted by the companies. This will be listed in stock exchange for secondary market. The investor decides whether to hold the stock for a longer or shorter period depending on the percentage of returns. Most of the research studies had concluded that Indian stock market is highly volatile, sensitive, reactive to news and unanticipated shocks. This instantly has an impact on the market trend activities, but it resilient and recovers soon. The investor aims for high returns on the investment, and experience a high risk . Since the direction of market is unpredictable and lack of knowledge for the success factors, leads to fear on investing in stock market. Practically the risk and returns are directly proportional. However the risk-return perceptions of the investor may vary.The aim of this study is to analyse acquaintance level of the investor in stocks trading and the technical knowledge to overcome the risk factors while trading in live market before investing.